2013
DOI: 10.1364/ao.52.004200
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid source mask optimization for robust immersion lithography

Abstract: To keep pace with the shrinkage of critical dimension, source and mask optimization (SMO) has emerged as a promising resolution enhancement technique to push the resolution of 193 nm argon fluoride immersion lithography systems. However, most current pixelated SMO approaches relied on scalar imaging models that are no longer accurate for immersion lithography systems with hyper-NA (NA>1). This paper develops a robust hybrid SMO (HSMO) algorithm based on a vector imaging model capable of effectively improving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…1 Source mask optimization (SMO) improves the lithography performance by co-optimizing the illumination source and mask. 2 The optimized mask structure and source shape via SMO suffers from extreme complexity, especially for the pixelated mask and source, [3][4][5] which leads to difficulty in manufacturing. Furthermore, the parameters related to the process, such as the film stacks, postexposure bake (PEB), and photoresist development, have a strong impact on the process window (PW).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 Source mask optimization (SMO) improves the lithography performance by co-optimizing the illumination source and mask. 2 The optimized mask structure and source shape via SMO suffers from extreme complexity, especially for the pixelated mask and source, [3][4][5] which leads to difficulty in manufacturing. Furthermore, the parameters related to the process, such as the film stacks, postexposure bake (PEB), and photoresist development, have a strong impact on the process window (PW).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 However, most published optimization technologies were implemented under fixed process conditions. 3,8,9 Moreover, lithography-tool parameters such as the numerical aperture (NA) and source parameter also determine the PW. 1 Actually, the parameters related to the mask, process, and lithography tool simultaneously impact the lithography performance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we proposed a pixelated SMO based on a vector imaging model that significantly improved the simulation precision for lithography at the 45-nm node and beyond. 11,12 Previous SMO methods fixed the NA and fell short in considering the mutual impact of the NA with respect to the source and mask. Prior work has demonstrated that a larger NA could realize a higher resolution, but the DOF would decrease because of the relation DOF ¼ k 2 · λ∕ðNAÞ 2 , 13 where λ is the wavelength and k 2 is the process factor.…”
Section: Introductionmentioning
confidence: 99%